PENGARUH QUALITY OF WORK LIFE DAN ISLAMIC WORK ETHIC TERHADAP LOYALITAS KARYAWAN PT. BANK SYARIAH INDONESIA - Olivia Avananda, Regina; Deki Hadiwibawa (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2024)
This research aims to determine the influence of Quality of Work Life and Islamic Work Ethics on Employee Loyalty of PT. Indonesian Sharia Bank. This research is quantitative research, the object of this research is employees of PT. Bank Syariah Indonesia Bengkulu branch with a sample of 60 respondents, using descriptive analysis techniques using the entire research population. Data was collected through questionnaires and analyzed using the multiple linear regression method. Based on the results of multiple linear regression, the regression equation Y = = Y = 9.485 + 0.356 (X1) + 0.214 (X2) is obtained. From the results of the hypothesis test, it shows that Quality of Work Life, namely thit (2.494 < 2.002 and (sig < a = .000 < 0.050) has a significant and influential effect on Employee Loyalty of PT. Bank Syariah Indonesia Bengkulu Branch., and Islamic Work Ethics, namely thit > ttable (3.167 > 2.002) and (sig < a = .000 < 0.050) have a significant effect on Employee Loyalty at PT Bank Syariah Indonesia Bengkulu branch.